PENGUATAN KOMPETENSI PEDAGOGIK GURU MELALUI PEMANFAATAN MEDIA DIGITAL DALAM PEMBELAJARAN DI MIS YAPPI KARANG, GUNUNGKIDUL (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine how to improve teachers' teaching abilities through the use of digital media in lessons at MIS YAPPI Karang, Gunungkidul. A descriptive qualitative method was employed, involving one principal, four teachers, and three students as subjects, along with classroom observations and the collection of learning documents. Data were gathered through in-depth interviews, structured observations, and documentation of digital media use. The results indicate that teachers have utilized digital tools such as Canva, Quizizz, Wordwall, instructional videos, and Google Classroom to make the learning process more effective. The use of digital media has positively impacted the enhancement of teaching abilities, particularly in lesson planning, classroom management, method selection, and learning evaluation. Students also responded very positively, showing increased participation, motivation, and conceptual understanding. However, several challenges remain, including inadequate infrastructure such as internet connectivity issues and varying levels of digital literacy among teachers. This study concludes that the use of digital media significantly supports the strengthening of teachers' teaching abilities and improves the quality of learning, although continuous facility support and training are still required.